Association of Plasma Bilirubin Levels With Peripheral Arterial Disease in Chinese Hypertensive Patients: New Insight on Sex Differences - Shi, Yumeng; Zhou, Wei; Cheng, Mingshu; Yu, Chao; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Hu, Lihua; Li, Ping; Cheng, Xiaoshu (Frontiers in Physiology, 2022)
Background and aims: Previous studies have indicated that Plasma total bilirubin (TBiL) might play an essential role in peripheral artery disease (PAD). However, the effects of different levels of TBiL on PAD development remain uncertain. We aimed to examine the TBiL and prevalence of PAD among Chinese adults with hypertension, with particular attention paid to sex differences. Methods: A total of 10900 hypertensive subjects were included in the current study. The mean age of our study participants was 63.86 ± 9.25 years, and there were 5,129 males and 5,771 females. The outcome was peripheral arterial disease (PAD), defined as present when the ABI of either side was ≤ 0.90. The association between TBiL and PAD was examined using multivariate logistic regression analysis and the restricted cubic spline. Results: Of 10900 hypertensive participants, 350 (3.21%) had PAD, and the mean plasma total bilirubin was 14.66 (6.86) μmol/L. The mean TBiL was 15.67 μmol/L in men and 13.76 μmol/L in women. The smoothing curve showed that a U-shaped curve association existed between TBiL and the prevalence of PAD in Chinese adults with hypertension. When stratified by sex, TBiL was significantly U-shaped associated with PAD in men but not in women. Among male, the inflection point was 11.48 μmol/L; on the left inflection point, the effect size and 95% CI were 0.08, 0.01, 0.66, respectively; on the right inflection point, OR, 5.16; 95% CI,1.64, 16.25. Conclusions: We found an independent U-shaped association between TBiL and the prevalence of PAD among hypertensive subjects and a differential association between men and women. We further revealed a turning point by threshold effect analysis.